Vitamin and mineral supplements - Misner, B.
Researchers have established both by application of reliable research and trial and error with world-class athletes, that the more one pushes their limits in training the more they tend to deplete necessary nutrients, vitamins, minerals, enzymes, coenzymes, and substrates. Athletes today ingest only 11% of the organic nutrients from their food sources that the athletes of the 1940s enjoyed. Why so little? The soils have been depleted by modern farming techniques; we have lost 89% of what the soils formerly gave to growing crops and livestock feed. Pesticides and pollutants within the harvested produce also have been observed to interfere with the complete absorption of vital organic substrates. As the athlete ages, no matter how good their inherited genetics, less digestive enzymes are produced (needed for maximal absorption of foods ingested). We are starving and nutrient-deficient, yet we are 33% overweight. Modern science has concluded that marginal nutritional deficiency and imbalance is directly responsible for 644 diseases or disorders. Credible research from several journals of science named a number of health and performance inhibiting disorders which may be caused by the marginal lack or imbalance of the following micronutrients: boron (3), calcium (31), copper (33), folic acid (37), iodine ( 6), iron (31), magnesium (47), manganese (14), niacinamide or Niacin (24), pantothenic acid (14), PABA (5), potassium (19), selenium (37), vitamin A (42), vitamin B-1 (19), vitamin B-2 (15), vitamin B-6 (40), vitamin B-12 (35), vitamin C (53), vitamin D (24), vitamin E (59), and zinc (56) or 644 possible performance-inhibiting, deficiency-induced problems, which athletes are experiencing today.